2020
DOI: 10.11591/ijece.v10i1.pp15-21
|View full text |Cite
|
Sign up to set email alerts
|

Overview on recent photovoltaic module cooling methods: advances PVT systems

Abstract: Renewable energy had been monopolized the research area in these past decade up till nowadays, due to its reliability and future in global production of electrical and thermal energy. Narrowing down the scope to the photovoltaic thermal (PVT) system, lots of improvements had been implied both theoretically and experimentally. One of the most attractive applications of PVT water or air-based collectors is building integrated photovoltaic thermal (BIPVT) system, which has undergone rapid developments in recent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The sensor collects the highest possible radiation from the sun (1283 W/m²) in full sunlight when the upper mirror is set at an angle of 5° and the lower mirror at an angle of 37°, these two angles are taken as the optimal angles to collect the maximum energy. To validate our theoretical results, we have compared them with the experimental described in [16], [15]. While respecting the same climate conditions as well as the properties of the system as shown in Table 1 during May 4 th and June 15 th , the comparison is made for the following parameters: the cell temperature, the total irradiation, the electrical power of the output and the output temperature of the fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor collects the highest possible radiation from the sun (1283 W/m²) in full sunlight when the upper mirror is set at an angle of 5° and the lower mirror at an angle of 37°, these two angles are taken as the optimal angles to collect the maximum energy. To validate our theoretical results, we have compared them with the experimental described in [16], [15]. While respecting the same climate conditions as well as the properties of the system as shown in Table 1 during May 4 th and June 15 th , the comparison is made for the following parameters: the cell temperature, the total irradiation, the electrical power of the output and the output temperature of the fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have been carried out PV/T air collectors, exploring aspects Int J Elec & Comp Eng ISSN: 2088-8708  Solar photovoltaic/thermal air collector with mirrors for optimal tilts (Assia Benkaddour) 2275 such as improving the efficiency by developing the design [13]. A review of the literature highlights that several studies have evaluated the ability of the nanofluid as a heat transfer fluid and optical filter in the PV/T system [14] as well as commenting on the advances in cooling techniques PV/T systems [15], [16]. The work of Tiwari et al [17] found that the total thermal efficiency of the photovoltaic/thermal system is greatly boosted by using the thermal energy of the module.…”
Section: Related Workmentioning
confidence: 99%
“…where ∆𝑝 is the pressure loss of the HTF pumpig [Pa], 𝑉 ̇ is the HTF flow rate [m 3 /s], and 𝑃 𝑖𝑛 is the solar power input to the system [W]. The overall efficiency ηo is expressed as in (2).…”
Section: Numerical Modelmentioning
confidence: 99%
“…This effect was led to achieve a maximum overall efficiency (ηo) of up to 80% for the PVT system [1]. The PVT systems differs in the cooling technique and fluids [2], [3]. So, the following paragraphs introduces the up-to-date research considering cooling techniques and fluids in PVT systems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the electrical efficiency, this excess heat is extracted by passing a heat extracting fluid (water or air) under the module. This integrated method, where thermal and electrical energy are generated simultaneously, is the basis of PVT collectors [1][2] [3][4].…”
Section: Introductionmentioning
confidence: 99%